2018
DOI: 10.1088/1555-6611/aab655
|View full text |Cite
|
Sign up to set email alerts
|

Switchable dual-wavelength single-longitudinal-mode erbium fiber laser utilizing a dual-ring scheme with a saturable absorber

Abstract: In this work, we propose and demonstrate a switchable dual-wavelength erbium-doped fiber (EDF) ring laser with stable single-longitudinal-mode (SLM) output. Here, a dual-ring (DR) structure with an unpumped EDF of 2 m is designed to achieve SLM oscillation. Five fiber Bragg gratings (FBGs) are applied in the laser cavity serving as the reflective element to generate different dual-wavelength outputs. In the measurement, six sets of generated dualwavelengths with various mode-spacing (Δλ) can be achieved via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Multi-wavelength switchable fiber lasers or dual-wavelength switchable fiber lasers are widely used in laser technology [1], fiber optic sensing [2], optical communication [3] and also in the design of optical division multiplexing mechanism (WDM) [2][3][4][5]. Multi-wavelength mode-locked and Qswitched pulses in fiber lasers have been successfully achieved using both active and passive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-wavelength switchable fiber lasers or dual-wavelength switchable fiber lasers are widely used in laser technology [1], fiber optic sensing [2], optical communication [3] and also in the design of optical division multiplexing mechanism (WDM) [2][3][4][5]. Multi-wavelength mode-locked and Qswitched pulses in fiber lasers have been successfully achieved using both active and passive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…However, adding multiple devices in the central station increases the overall cost of the transmission system. In [19][20][21], semiconductor optical amplifiers (SOAs) and erbium-doped fiber amplifiers (EDFAs) are utilized as gain mediums to generate multi-wavelengths. Although EDFA has the characteristics of a flatter gain spectrum, lower polarization-dependent gain, and higher saturation power, it has a strong line broadening and cross-saturation at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Anum et al [13] reported a single-and dual-wavelength tunable ring-cavity EDF laser based on the Fabry-P erot (FP) structure, and was fabricated by single-mode fibers (SMFs) and multimode fibers. Additionally, Yang et al [14] realized a dual-wavelength switchable fiber laser based on a double-ring cavity, while six different groups of lasing conditions were obtained for the proposed fiber laser. Xu et al [15] designed and realized a switchable single-mode fiber laser based on a h shaped microfiber filter.…”
Section: Introductionmentioning
confidence: 99%